Development of Perilla seed oil and extra virgin olive oil blends for nutritional, oxidative stability and consumer acceptance improvements. (15th July 2019) - Torri, Luisa; Bondioli, Paolo; Folegatti, Liliana; Rovellini, Pierangela; Piochi, Maria; Morini, Gabriella
Highlights: Blends of Perilla seed oil (PO) and extra virgin olive oil (EVOO) were developed. Blends were high in ω − 3 and ω − 6 fatty acids, biophenols, tocopherols, and sterols. Blends showed higher oxidation stability than PO. All blends reached the sensory acceptability by consumers. Blends with 25–35% and 40–45% PO were paired respectively with raw and cooked foods. Abstract: This study reports the blending at different levels (25, 30, 35, 40 and 45%) of Perilla seed oil (PO) with extra virgin olive oil (EVOO). Pure oils and blends were evaluated in terms of free acidity, peroxide value, fatty acid composition, sterols, tocopherols and biophenols content, oxidation stability, sensory acceptability and food pairing. Blends with high content of ω − 3 and ω − 6 fatty acids, biophenols, tocopherols, sterols and satisfying oxidation stability were obtained, representing products with improved nutritional properties. All blends resulted acceptable by consumers. Two groups of consumers with opposite preferences for samples with low (25–35%) and high (40–45%) levels of PO were identified. Blends containing 40–45% of PO were mainly paired to strong-flavour and cooked foods, while blends with less PO were preferably matched with raw meat and vegetables. Consequently, PO and EVOO blends showed promising potential as innovative vegetable oils with improved nutritional properties and versatile gastronomic use.